Optimal Operation Strategy for Rural Microgrid Considering Greenhouse Load Control - Xueqian Fu; Yazhong Zhou; Zhonghui Wei; Yang Wang (CSEE Journal of Power and Energy Systems)
Impact of rural electrification is picking up, which has changed the energy structure and significantly reduced greenhouse gas emissions in rural areas. At present, due to separation management of agricultural and energy systems, agricultural cost is high, and new energy consumption in the local microgrid is small, but carbon emission is high. We propose a novel optimal operation strategy for a rural microgrid considering greenhouse load control, which is greenhouse environment control. We establish a greenhouse load control model, including an artificial lighting model, a heating load model, and a load shifting model. Our characteristic work is to establish a carbon dioxide model of greenhouse consumption, and we build a unique optimal operation model of a rural microgrid by combining control of carbon dioxide and control of the energy system. We simulate a rural microgrid with wind power, photovoltaic, gas-fired boiler, and cogeneration system. Summer and winter scenarios are used for analysis, as energy consumption patterns in greenhouses during these seasons are highly representative. Results show the proposed optimization strategy can effectively cut operating expenses for the rural microgrid, improve rate of new energy consumption in the local microgrid, and reduce carbon dioxide emissions.